Priority directions for the development of regional health care centers conducting organ transplantation - Kovtun, Gavrylo (The Ukrainian Scientific Medical Youth Journal, 2023)
to form a medical and social substantiation of priority areas for the development of re- gional health care centers conducting organ transplantation. For the achievement of the goal, the funda- mental scientific methods of analysis, synthesis, aggregation, interpretation of scientific data, as well as systemic analysis, were put in place. Medical and sociological follow-up of 411 patients was carried out in the clinic at the Institute of Heart of the Ministry of Health of Ukraine, 453 doctors – anesthesiologists in the communal health departments of the Ministry of Health of Ukraine and 417 doctors – neuropa- thologists in the community health departments of the Ministry of Health of Ukraine. The analysis of the forms of state statistical and expert evaluation of the structural and organizational activities of the basic system of donation and organ transplantationin Ukraine was carried out. Ananalysis of the state of regional health care centers conducting transplantations and an expert assessment of the structural and organizational storage activities of the system of donation and organ transplantation in Ukraine showed that the National Strategy for the Development of Donation and Organ Transplantation has not been developed, funding and material and technical base, and professional training of regional healthcare. There are no developed and officially approved national protocols and clinical guidelines for organ transplantation, qualification characteristics for transplant-coordinators. The mentality of organ donation and transplantation in the country is not at a high level. The analysis of the forms of national statistical ranks howed that diseases of the circulatory system are the leading cause of premature death and disability in the population of Ukraine, which determines their significant medical, social and so- cio-economic significance. A sociological study conducted among patients made it possible to establish that the prevailing cultural perceptions of Ukrainians currently do not create positive precedents for the development of donation based on the solidarity system of “organ testament”. A sociological study conducted among doctors – neuropathologists showed that the awareness of neuropathologists about the modern possibilities of transplantology is weak, there is not enough knowledge about the technique of donor organ transplantation, and there is no positive motivation for organ donation. The identified problems confirmed that the conditions in which health care providers conduct transplants work, in- creasing the volume of transplants that contribute to the preservation of public health, and often life, is problematic. The study contributed to the formation of priority are as for the development of regional health care providers conducting organ transplantation.